'Some Hae Meat': The Development of the Burns Supper Menu from 1801 to Today. Issue 2 (September 2021) - McGinn, Clark
Abstract : When the first Burns Supper was conceived in 1801 as a convivial club dinner commemorating Robert Burns and performing his poems and songs, a central trope was the inclusion of traditional Scottish dishes. While the haggis, and its attendant 'address' were, and remain central to the concept, the other food on the menu has been influenced by culinary fashion, regionalism, politics and cross-cultural fusion.